Principio de mínima intervención penal en contravensiones por lesiones. - Velastegui Guilcapi Omar Wilfrido (2024)
Criminal law conceptualized in various ways as the different schools focus on the study of crimes and contraventions, which are generally understood as infractions, and establishes criminal sanctions respecting the principle of proportionality. The main objective is to regulate human behavior to maintain social order and protect the rights and safety of citizens. Criminal law is understood as a last resort for the protection of legal assets that are protected by substantive criminal law, and it is understood that the criminal legal system must intervene to the least possible extent in the lives and freedoms of people. This is called minimum criminal intervention, which is a principle that is based on the idea that the State's intervention in individual matters must be limited and justified, and that criminal responses must be proportional to the crime or contravention committed. The Ecuadorian criminal regulations establish several extra-penal mechanisms that, respecting the guidelines of the procedure, can be applied to avoid the sanctioning power of the state, such as the principle of opportunity, conciliation in the regulated conditions, from the adjective field the abbreviated procedure, the conditional suspension of sentence, etc. Of legal institutions, the conditional suspension of the sentence stands out in the investigation, which, as structured in Ecuador, would apply only to crimes. The principle of minimal criminal intervention in contraventions involving injury to a person is an area of research that focuses on examining how this principle is applied in legislation and judicial practice. The research examines how our legal system handles minor injury cases, assessing whether criminal responses are proportional to the harm caused and whether the use of alternatives to incarceration is promoted. The purpose of this investigation is to identify the consequences of extra-penal mechanisms in Ecuadorian criminal law, in cases of fourth class contraventions due to 18 injuries established in article 396, numeral 4 of the Ecuadorian Comprehensive Criminal Organic Code, because there are contradictions regarding the application of the conditional suspension of the sentence established in article 630 ibidem, its application not being allowed in cases concerning article 396 numeral 4 ibidem, while it is allowed for individuals who are being prosecuted for injuries established in article 152 numerals 1 and 2. For the success of this research, the mixed method will be applied that will be used to collect, analyze and combine, either integrating or connecting, both quantitative and qualitative data, background information obtained according to the research, concomitantly, research instruments such as the surveys and interviews, carried out with expert professionals in the criminal area, will refer to the application of the Principle of Minimum Criminal Intervention in Fourth Class Contraventions. Keywords: Minimum criminal intervention, proportionality, contravention, extra-penal mechanisms, conditional suspension of sentence.